OPTIMALISASI TERMOELEKTRIK MELALUI HEAT GAIN SEBAGAI PENGHASIL LISTRIK - Lukman Nulhakim (Jurnal Elektra, 2019)
Thermoelectric is an energy conversion device converting heat energy into electrical energy consisting of p-type and n-type semiconductor materials connected in series packaged using ceramic as its wall. The thermoelectric used in the TEC1-12706 model is assembled with 2 heatsinks with an extrude model. The test is carried out every 30 seconds for 10 minutes using the temperature of the heat produced with the media of water that has been heated, while to cool using free air. The highest voltage and power produced are 1,797 mV and 125.79 mW at the hot side temperature of 85.4 oC and the cold side temperature of 65.6 oC with a time of 510 seconds.